Reducing Water Footprint in Portland Cement Concrete Manufacturing - Nagy, Mohamed (AUC Knowledge Fountain, 2024)
Despite water covering roughly 71 percent of the Earth's surface in various forms, including oceans, seas, ice caps, glaciers, lakes, and atmospheric moisture, there is a looming crisis concerning freshwater availability. Wastage occurs across diverse sectors such as households, commercial establishments, industries, agriculture, and transportation hubs. For instance, an average household squanders around 70 gallons (265 liters) of water per day. Moreover, the concrete industry significantly contributes to water consumption, utilizing approximately 16.6 × 109 m3 annually, with each square meter of construction requiring about 410 liters of water. This wastage occurs throughout the concrete manufacturing process, prompting the necessity to explore direct and indirect methods to curtail freshwater consumption, both within the production process and the concrete mix itself. This study aims at providing a comprehensive understanding of the state of freshwater footprint in the concrete industry to seek means to reduce its consumption without compromising on its performance. To achieve this objective, the research proposes conducting comprehensive case studies involving concrete factories and stone crushers to assess current water usage and waste levels. By scrutinizing various stages of production, from raw material extraction to finished product manufacturing, the research aims to pinpoint areas where water conservation measures can be implemented effectively. Additionally, our investigation extends to examining efforts made by factories to diminish wastewater generation, thereby addressing environmental concerns, and promoting sustainable practices within the industry. Extensive research revealed that the primary concrete-producing countries are facing notable water stress. Moreover, there's a limited number of studies globally addressing the water footprint in concrete manufacturing, with none originating from the Middle East. This underscores the significance of this research as a crucial starting point for addressing the water footprint in concrete manufacturing and devising strategies to mitigate it.